1990
DOI: 10.1109/50.50759
|View full text |Cite
|
Sign up to set email alerts
|

Frequency response theory for multilayer photodiodes

Abstract: An exact solution is developed for the frequency response of photodiodes composed of multiple spatially uniform layers. Each layer is analyzed separately to obtain a set of linear response coefficients. The response of the multilayer diodes is calculated using matrix algebra. Effects of carrier transit, electron and hole tapping, avalanche decay, and finite absorption length are included in the analysis. The results of Emmons and Lucovsky for APD's and p-i-n's are obtained as special cases. The theory is illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Regarding the transit time effects, the frequency response is calculated by combining the coefficients derived from a matrix formulation, following the analytical solution of the continuity equations in the drift and absorption regions [6]. The analytical solutions can be obtained only for constant drift carrier velocities, i.e., when the electric field is constant.…”
Section: Transit Time Effectsmentioning
confidence: 99%
“…Regarding the transit time effects, the frequency response is calculated by combining the coefficients derived from a matrix formulation, following the analytical solution of the continuity equations in the drift and absorption regions [6]. The analytical solutions can be obtained only for constant drift carrier velocities, i.e., when the electric field is constant.…”
Section: Transit Time Effectsmentioning
confidence: 99%
“…Using a similar local analysis [12], [13] concluded that a gain-bandwidth product of 228 GHz should be achievable using an APD with a 0.1 m bulk InAlAs multiplication layer [13]. However, at such small dimensions, the dead space becomes a significant fraction of the avalanche width.…”
Section: Introductionmentioning
confidence: 99%
“…This source of dark current can be suppressed by isolating the low-bandgap material in a dedicated absorption layer in which the electric field is moderated by an adjacent charge layer: the separate absorption, charge, and multiplication (SACM) design, as diagramed in Fig. 1 [7]. SACM APDs can also be modulated faster than homojunction APDs because photogeneration of carriers is confined to a single layer, which shortens the impulse response of the detector [7,8].…”
Section: Epitaxially-grown Sacm Apdsmentioning
confidence: 97%